Conditionally Reprogrammed Cells and Robotic High-Throughput Screening for Precision Cancer Therapy - Alkhilaiwi, Faris (Frontiers in Oncology, 2021)
Cancer is a devastating disease that takes the lives of millions of people globally every year. Personalized cancer treatment is based on a patient’s tumor histopathology, expression analyses, and/or tumor RNA or DNA analysis. Only 2–20% of patients with solid tumors benefit from genomics-based precision oncology. Therefore, functional diagnostics and patient-derived cancer models are needed for personalized cancer therapy. In this review, we will summarize the potential use of conditional cell reprogramming (CR) and Robotic high throughput screening in personalized cancer medicine. Briefly, the CR method includes the co-culturing of irradiated Swiss-3T3-J2 mouse fibroblasts cells alongside digested primary non-pathogenic or pathogenic cells with the existence of Rho-associated serine-threonine protein kinases inhibitor called Y-27632, creating an exterior culture environment allowing the cells to have the ability to gain partial properties of stem cells. On the other hand, quantitative high throughput screening (qHTS) assays screen thousands of compounds that use cells in a short period of time. The combination of both technologies has the potential to become a driving force for personalized cancer treatment.